2014
DOI: 10.1038/sc.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Medication before and after a spinal cord lesion

Abstract: Objective: To map the impact of spinal cord lesion (SCL) on medication. Study design: Registration of medication for 72 patients before SCL and at discharge from the Department for Spinal Cord Injuries. Setting: Department for Spinal Cord Injuries, East Denmark. Methods: The changes in medication for each Anatomical Therapeutic Chemical (ATC) Classification System group were registered for all patients, who were discharged from Department for Spinal Cord Injuries during 2010. The changes in medication per se w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Polypharmacy in patients with SCI is common, as was observed in our study as well as in a prospective study conducted among 72 patients with spinal cord lesion 5 and a retrospective case-control analysis of 13,160 individuals with SCI. 6 However, in comparison to the retrospective case-control study, we found a higher rate of polypharmacy (74%) when all products were considered, as well as when polypharmacy was limited to prescribed and over-the-counter medications (63% vs 56%).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Polypharmacy in patients with SCI is common, as was observed in our study as well as in a prospective study conducted among 72 patients with spinal cord lesion 5 and a retrospective case-control analysis of 13,160 individuals with SCI. 6 However, in comparison to the retrospective case-control study, we found a higher rate of polypharmacy (74%) when all products were considered, as well as when polypharmacy was limited to prescribed and over-the-counter medications (63% vs 56%).…”
Section: Discussionmentioning
confidence: 65%
“…Jensen and colleagues 5 have documented an increase in medication intake by patients recently diagnosed with SCI in an acute care environment and Kitzman and colleagues 6 have demonstrated significantly higher rates of polypharmacy, use of high-risk medications, and occurrence of adverse drug events in patients with SCI on polypharmacy. However, neither study described the prevalence of pharmacotherapy, polypharmacy, or types of medication use among the SCI populations served by a primary care-based clinic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Persons with SCI/D may experience multiple secondary health complications [3][4][5] and comorbid conditions. [6][7][8] As a result, treatment plans are often complex, 9,10 involving the concomitant use of multiple medications (i.e. polypharmacy), [11][12][13][14] which often include high-risk prescription drugs (e.g.…”
Section: Spinal Cord Injury and Dysfunction (Sci/d) Can Results In Permentioning
confidence: 99%
“…27 Although medication adherence is a primary determinant for the successful treatment of chronic conditions, 27,28 approximately half of all persons with chronic conditions in developed countries do not take their medications as prescribed. 27,29 The high instances of polypharmacy 9,13 and health and social complexities 1 in the SCI/D population underscore the need for further research into medication adherence. Through effective communication and patient-centered care, healthcare providers can play a pivotal role in improving medication adherence and self-management behaviors of patients experiencing polypharmacy.…”
Section: Spinal Cord Injury and Dysfunction (Sci/d) Can Results In Permentioning
confidence: 99%